Thickness-dependent shear localization in Cu/Nb metallic nanolayered composites. (October 2020) - Dong, Shujing; Chen, Tianju; Huang, Sixie; Li, Nan; Zhou, Caizhi
Abstract: We performed molecular dynamics simulations to study the effect of the layer thickness on the shear localization in Cu/Nb metallic nanolayered composites (MNCs). Our simulation results achieve good agreement with experimental results that the inverse size effect in the strength occurs in samples with layer thickness below 2.0 nm. The strain softening observed in those samples was triggered by the shear localization. The quantitative analysis revealed that the unsymmetrical dislocation transmission across the interface induces the shear localization and promotes the shear band formation in Cu/Nb MNCs. The plastic strain mainly comes from the interface sliding within the shear band. Graphical abstract: Sequential snapshots of (a) von Mises shear strain distributions and (b) atomistic configurations for the 1.35 nm sample deformed at different strain levels. Image, graphical abstract